Analisis Tematik Hadis tentang Kerjasama Modal dalam Perspektif Syariah - Hafid, Abd.; Kara, Aisyah; Ahmad, Arifuddin (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2025)
This research aims to analyze capital cooperation as discussed in several Hadith collections. Therefore, it employs the maudhui (thematic) method to examine various Hadiths concerning capital cooperation found across different Hadith compilations. This examination delves into the ontological, epistemological, and axiological aspects of Hadiths on capital cooperation, specifically how they manifest social worship in economic activities as a form of social responsibility. The findings indicate that there are approximately 50 Hadiths related to capital cooperation that use the term "al-syarikah" (Ø§Ù„Ø´Ø±ÙƒØ©) and around 12 Hadiths that use the term "al-ikhtilath" (Ø§Ù„Ø¥Ø®ØªÙ„Ø§Ø·). In Islamic jurisprudence literature, the practice of "capital cooperation" is categorized under al-syirkah, which in Indonesian is translated as "perserikatan" or "perkongsian" (partnership or association). The term al-syirkah in al-Munjid is defined as al-ikhtilath, meaning "to mix" or "to blend." Islam views cooperation as a means of mutual assistance in driving human productivity, which holds the value of social worship. Consequently, it is crucial to maintain, preserve, and foster cooperation to achieve human well-being in both this world and the hereafter. Capital cooperation, as a primary medium for achieving shared prosperity, also serves as an implicit prohibition against hoarding capital. A Muslim who possesses wealth is commanded to assist others as a form of social responsibility. This research recommends that everyone distribute a portion of their capital to help those who lack it in running their businesses, as a form of humanitarian social responsibility.Penelitian ini bertujuan untuk menganalisis kerjasama modal dalam beberapa kitab Hadis. Oleh karena itu, penelitian ini menggunakan metode maudhui (tematik) dalam mengkaji beberapa hadis tenteng kerjasama modal yang tersebar di beberapa kitab hadis, baik secara Ontologis, Epitemologis dan Aksiologis mengenai hadis kerjasama modal dalam mengejawantahkan aspek ibadah sosial pada aktifitas ekonomi, sebagai bentuk tanggung jawab sosial. Temuan penelitian ini menunjukkan bahwa hadis-hadis yang terkait dengan kerjasama modal dengan menggunakan lafal al-syarikah berjumlah kurang lebih 50 buah8 dan yang menggunakan lafal al-ikhtilath berjumlah kurang lebih 12 buah.9 Kerjasama dalam literatur fikih dikatakan bahwa praktek â€œkerjasama modalâ€ termasuk dalam bentuk al-syirkah (Ø§Ù„Ø´Ø±ÙƒØ©), yang dalam bahasa Indonesia diistilahkan dengan â€œperserikatanâ€ atau â€œperkongsianâ€. Term al-syirkah dalam al-Munjid diartikan dengan al-ikhtilath (Ø§Ù„Ø¥Ø®ØªÙ„Ø§Ø·),2 artinya; ber-campur. Islam memandang bahwa kerjasama sebagai sarana tolong menolong dalam menggerakakan produktifitas kehidupan manusia yang bernilai ibadah sosial, sehingga sangat penting dijaga,dipelihara dan diperhatikan untuk mewujudkan kemaslahatan manusia di dunia maupun di akhirat; Kerjasama modal, sebagai mediumÂ  utama dalam memenuhi kesejahteraan bersama, sekaligus sebagai isyarat larangan menimbun modal, seorang muslim yang memiliki harta diperintahkan untuk membantu orang lain sebagai bentuk tanggung jawab sosial. Penelitan ini merekomendasikan agar setiap orang mendistribusikan sebagian modalÂ  mereka untuk membantu sesamanya yang kekurangan modal dalam menjalankan usahanya sebagai bentuk tanggung jawab sosail kemanusiaan.